Views from Inside and Outside: Integrating Emic and Etic Insights about Culture and Justice Judgment - Morris, Michael W.; Leung, Kwok; Ames, Daniel R.; Lickel, Brian (Academy of Management Review, 1999)
We analyze forms of synergy between emic and etic approaches to research on culture and cognition. Drawing on the justice judgment literature, we describe dynamics through which the two approaches stimulate each other's progress. Moreover, we delineate ways in which integrative emic/etic frameworks overcome limitations of narrower frameworks in modeling culture and cognition. Finally, we identify advantages of integrative frameworks in guiding responses to the diverse justice sensitivities in international organizations.